Sistematización de medición del proceso de clima laboral en Novaclínica S.A. y diseño de un plan de mejora - Chiluiza Fernández, María Fernanda (2018)
The present work carries out the systematization of the design experience of a measurement methodology of the work environment and the planning of an improvement plan for NOVACLÍNICA located in the Metropolitan District of Quito. The research was developed with the use of tools such as observation, interviews and the application of a survey. The population surveyed was all the employees of NOVACLÍNICA that were 220 people. The improvement plan was developed based on the dimensions that had weaknesses in the company. The present work is relevant because it demanded that the theoretical knowledge acquired in the psychology degree be applied to practice. In addition, the relevance of the participation of a work psychologist inside the company was established. The main motivation of the systematization work was to contribute with the evaluation of NOVACLÍNICA's work environment and, based on the results obtained, to propose an improvement plan.